A large-scale mixed reality stadium for training coordinated tactical plays in basketball - Saiki, Hayato; Hirokawa, Masakazu; Hassan, Modar; Suzuki, Kenji (Frontiers in Virtual Reality, 2026)
In recent years, virtual, augmented, and mixed reality (MR) technologies have gained increasing attention in sports training for their potential to improve motor skills and team coordination. However, existing systems predominantly emphasize individual skills or small-scale settings, offering limited support for realistic multi-player, full-court tactical training. To address this gap, this paper proposes a large-scale mixed reality environment for training coordinated tactical plays in basketball. In this environment, players can practice various tactics such as ball passing and screens with virtual players and visual instructions overlaid in the real environment using a see-through head-mounted display. Two evaluation experiments were conducted. In Experiment 1, expert players performed pick-and-roll plays in both MR and real environments. The results showed no significant differences in execution time or movement trajectories, suggesting that the MR environment may offer spatial and temporal consistency comparable to real play. In Experiment 2, novice players trained with the MR system and with a conventional method in real space. The results showed higher improvements in both spatial positioning and timing in the MR environment, suggesting it could support the training of coordinated tactical plays. These findings suggest the potential of MR technology for skill training involving multiplayer coordination in realistic tactical scenarios.